2000
DOI: 10.1084/jem.191.10.1755
|View full text |Cite
|
Sign up to set email alerts
|

A Key Role for Cc Chemokine Receptor 4 in Lipopolysaccharide-Induced Endotoxic Shock

Abstract: CC chemokine receptor (CCR)4, a high affinity receptor for the CC chemokines thymus and activation-regulated chemokine (TARC) and macrophage-derived chemokine (MDC), is expressed in the thymus and spleen, and also by peripheral blood T cells, macrophages, platelets, and basophils. Recent studies have shown that CCR4 is the major chemokine receptor expressed by T helper type 2 (Th2) polarized cells. To study the in vivo role of CCR4, we have generated CCR4-deficient (CCR4−/−) mice by gene targeting. CCR4−/− mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
217
7
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(241 citation statements)
references
References 39 publications
(47 reference statements)
14
217
7
1
Order By: Relevance
“…Furthermore, at 42 days Foxp3 was significantly lower in grafts from Ccr5 À/À than WT recipients. A similar expression pattern was observed for the chemokine receptor Ccr4, which is found on Th2 cells and Treg and involved in mediating their immunosuppressive effects [27,28]. The chemokine receptor Ccr7, which is upregulated in mature DC and also required for the in vivo function of Treg [29], showed significantly lower expression levels in Ccr5 À/À recipients at 42 days, but not at 7 days.…”
Section: Gene Expression Analysis In Renal Allograftssupporting
confidence: 66%
“…Furthermore, at 42 days Foxp3 was significantly lower in grafts from Ccr5 À/À than WT recipients. A similar expression pattern was observed for the chemokine receptor Ccr4, which is found on Th2 cells and Treg and involved in mediating their immunosuppressive effects [27,28]. The chemokine receptor Ccr7, which is upregulated in mature DC and also required for the in vivo function of Treg [29], showed significantly lower expression levels in Ccr5 À/À recipients at 42 days, but not at 7 days.…”
Section: Gene Expression Analysis In Renal Allograftssupporting
confidence: 66%
“…18 Later studies indicated that CCL22 was responsible for progressive increase in CCR4-positive cells in more chronic allergic airway responses to ovalbumin. 22 The relative role of CCL17 and CCL22 in these responses has been questioned by other data showing that targeting CCR4 either by gene deletion 20 or specific antibody 21 fails to prevent the development of allergic airway responses although CCR4 does appear to be involved in the maintenance of chronic allergic responses to Aspergillus fumigatus. 23 The present study confirmed that CCL22 and CCL17, in part, are critical for the development of aggressive Th2 granulomatous responses in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased CCR4 8 -11 and its corresponding ligands CCL17 (TARC) [12][13][14][15][16] and CCL22 (MDC) 14,15,17 have been detected in various clinical samples from asthmatic and allergic patients. However, the relative role for these chemokines and its receptor in experimental forms of these diseases remains controversial because some groups report a role for CCL17 18 and CCL22 19 but a lack 20,21 or partial 22,23 role for CCR4 during Th2-type cytokine-driven allergic airway responses in mice.…”
mentioning
confidence: 99%
“…Curiously, at higher concentrations, MDC appeared to cause a reduction in the baseline numbers of basophils that were in the high FSC gate, an effect not seen with other chemokines. This may reflect basophil responses mediated by another MDC receptor, the existence of which has been speculated in other work (56).…”
Section: Discussionmentioning
confidence: 99%